The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/nrrheum.2014.137
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β—at the centre of systemic sclerosis

Abstract: Transforming growth factor β (TGF-β) has long been implicated in fibrotic diseases, including the multisystem fibrotic disease systemic sclerosis (SSc). Expression of TGF-β-regulated genes in fibrotic skin and lungs of patients with SSc correlates with disease activity, which points to this cytokine as the central mediator of pathogenesis. Patients with SSc often develop pulmonary arterial hypertension (PAH), a particularly lethal complication caused by vascular dysfunction. Several genetic diseases with vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
250
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(260 citation statements)
references
References 160 publications
6
250
0
4
Order By: Relevance
“…Our results show that pericytes of patients with SSc express the activated form of ADAM12 molecule, and that TGF-β, the main profibrotic cytokine in SSc 26,35,36,37,38 , modulates ADAM12 expression on these cells. These data suggest that, as observed in other experimental models of fibrosis, perivascular cells may be committed to transdifferentiate toward activated myofibroblasts and are involved in the fibrotic lesions of SSc.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our results show that pericytes of patients with SSc express the activated form of ADAM12 molecule, and that TGF-β, the main profibrotic cytokine in SSc 26,35,36,37,38 , modulates ADAM12 expression on these cells. These data suggest that, as observed in other experimental models of fibrosis, perivascular cells may be committed to transdifferentiate toward activated myofibroblasts and are involved in the fibrotic lesions of SSc.…”
Section: Discussionmentioning
confidence: 79%
“…In fact, lineage tracing experiments, in an experimental model of kidney fibrosis 19 , confirmed that these cells are the main source of myofibroblasts, and the perivascular progenitor cells, with a profibrotic function, may be identified by the expression of 1 specific marker, the isoform 12 of ADAM (ADAM12) 20 . It is well known that the main expression of ADAM12 may be observed during embryonic morphogenesis of skeletal muscles and visceral organs, and intriguingly this molecule may be newly expressed in several human fibrotic diseases 21,22,23,24,25,26 . Previously, we showed that because mesenchymal progenitors, which are generally considered an alternative source of functional pericytes 27,28 , exhibit the same phenotype and ability to differentiate of mature pericytes obtained from patients with SSc, they are involved in the generation of myofibroblasts in this disease 3,4,5,14 .…”
mentioning
confidence: 99%
“…Considerable attention has focused on transforming growth factor (TGF)-betriggered conversion of mesenchymal lineage cells to a-smooth muscle actin (SMA)epositive myofibroblasts as the central event in fibrosis. 3,4 Recently, elegant fate-mapping strategies have been used in the mouse to define the origin of these myofibroblasts and potentially the fibrotic process. 5e7 Indeed, a separate fibroblast lineage with enhanced fibrogenic potential was revealed using these methods.…”
mentioning
confidence: 99%
“…Among all the cytokines found to be up-regulated in SSc, especially in the skin and lung, TGF-β is a potent stimulator of extracellular matrix production and has been widely studied and reviewed [13]. It plays an important role in wound healing and tissue repair, and an aberrant regulation of TBG-β is associated with inherited conditions, such as hereditary haemorrhagic telangiectasia, familial pulmonary hypertension and Marfan syndrome, and with fibrotic diseases, such as liver cirrhosis and idiopathic pulmonary fibrosis.…”
Section: Main Physiopathological Mechanisms With Specific Treatment Pmentioning
confidence: 99%